PENGARUH POLITICAL CONNECTION TERHADAP TAX AGGRESSIVENESS DENGAN KOMITE AUDIT EXPERTISE SEBAGAI MODERATOR - Yisrael Antonnius Petra Yesianda (2021)
This study aims to determine the effect of political connection on tax aggressiveness with the audit expertise committee as the moderator variable. This study also uses return on assets, leverage and firm size as control variables. Tax aggressiveness as the dependent variable is proxied by the measurement of ABTD. Political connection as an independent variable is proxied by political connection board of commissioners and political connection board of directors. This study uses secondary data in the form of company annual reports with a sample of 69 non-financial state-owned companies. The analysis method used is panel data linear regression analysis with the random effect data method and using STATA version 12. Based on the results of data analysis it can be concluded that if the political connection board of directors has no effect on tax aggressiveness then the political connection board of commisioners has a positive effect and significant to the tax aggressiveness. For the moderator variable in this study, the audit expertise committee was unable to moderate the relationship between political connection and tax aggressiveness